Predisposition of Neonatal Maternal Separation to Visceral Hypersensitivity via Downregulation of Small-Conductance Calcium-Activated Potassium Channel Subtype 2 (SK2) in Mice - Ke Wu; Jing-hua Gao; Rong Hua; Xiao-han Peng; Hui Wang; Yong-mei Zhang (Neural Plasticity)
Background. Visceral hypersensitivity is a common occurrence of gastrointestinal diseases such as irritable bowel syndrome (IBS), wherein early-life stress (ELS) may have a high predisposition to the development of visceral hypersensitivity in adulthood, with the specific underlying mechanism still elusive. Herein, we assessed the potential effect of small-conductance calcium-activated potassium channel subtype 2 (SK2) in the spinal dorsal horn (DH) on the pathogenesis of visceral hypersensitivity induced by maternal separation (MS) in mice. Methods. Neonatal mice were subjected to the MS paradigm, an established ELS model. In adulthood, the visceral pain threshold and the abdominal withdrawal reflex (AWR) were measured with an inflatable balloon. The elevated plus maze, open field test, sucrose preference test, and forced swim test were employed to evaluate the anxiety- and depression-like behaviors. The expression levels of SK2 in the spinal DH were determined by immunofluorescence and western blotting. The mRNA of SK2 and membrane palmitoylated protein 2 (MPP2) were determined by quantitative real-time polymerase chain reaction (qRT-PCR). Electrophysiology was applied to evaluate the neuronal firing rates and SK2 channel-mediated afterhyperpolarization current (IAHP). The interaction between MPP2 and SK2 was validated by coimmunoprecipitation. Results. In contrast to the naïve mice, ethological findings in MS mice revealed lowered visceral pain threshold, more evident anxiety- and depression-like behaviors, and downregulated expression of membrane SK2 protein and MPP2 protein. Moreover, electrophysiological results indicated increased neuronal firing rates and decreased IAHP in the spinal DH neurons. Nonetheless, intrathecal injection of the SK2 channel activator 1-ethyl-2-benzimidazolinone (1-EBIO) in MS mice could reverse the electrophysiological alterations and elevate the visceral pain threshold. In the naïve mice, administration of the SK2 channel blocker apamin abated IAHP and elevated spontaneous neuronal firing rates in the spinal DH neurons, reducing the visceral pain threshold. Finally, disruption of the MPP2 expression by small interfering RNA (siRNA) could amplify visceral hypersensitivity in naïve mice. Conclusions. ELS-induced visceral pain and visceral hypersensitivity are associated with the underfunction of SK2 channels in the spinal DH.